Assessing the Use of Crushed Rock Aggregate and Carbon Black for Laterite Soil Stabilization in Road Construction. - Turyamureeba, Emmanuel (Kabale University, 2024)
The increasing demand for crushed rock aggregates in road construction has significantly contributed to the depletion of rock resources in Uganda. This research and design project aimed to explore the use of carbon black to reduce the volume of crushed rock aggregates required for the mechanical stabilization of lateritic soils for road base construction. Lateritic soil samples were collected from a borrow pit near Nyakambu, 1 km from Kekubo town along the Kekubo-Kikungiri Road. Crushed rock aggregates ranging from 0.075 mm to 10 mm in size were sourced from a quarry near the Faculty of Engineering, approximately 2 km from Kabale town off the Kabale-Kisoro Road. Carbon black was procured from GM Tire Recycling Plant in Njeru, Eastern Uganda (00°22’42.9” N, 33°08’10.4” E). Preliminary tests, including Particle Size Distribution, Atterberg Limits, Maximum Dry Density, and California Bearing Ratio (CBR), were conducted to assess the suitability of the lateritic soil for stabilization. The results classified the soil as Clayey Gravel with Sand of high plasticity according to the Unified Soil Classification System (USCS), confirming the need for stabilization for road base use. The combined effect of carbon black and crushed rock aggregates was evaluated based on compaction characteristics, Atterberg Limits, Particle Size Distribution, and CBR tests. Graphical analysis of the results revealed that a blend of 50% lateritic soil, 40% aggregates, and 10% carbon black was the most effective, yielding a CBR of 63.0 at 98% relative compaction and a Plasticity Index (PI) of 6.5. These results meet the General Specifications for Roads and Bridges by Uganda’s Ministry of Works, Housing, and Communication, which require a CBR above 60%. The study concluded that replacing the conventional 50% aggregates and 50% lateritic soil mixture (as suggested by Jjuuko et al., 2014) with the proposed blend reduces crushed rock aggregate consumption by 10%. The research successfully met all its objectives and demonstrated a sustainable approach to road base construction by incorporating carbon black.